Peningkatan Pengenalan Geometri Melalui Media Puzzle Bervariasi Dari Bahan Bekas - Anita, Mira; Sari, Rika Partika; Haryono, Mimpira (Journal Of Dehasen Educational Review, 2022)
The purpose of this study was to find out whether through the application of various puzzle media from used materials can increase the recognition of geometry in group B children at PAUD LAGAN PERTIWI in Group B, Seluma Barat District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were group B children, totaling 17 children. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing social emotional abilities in children in the PAUD LAGAN PERTIWI Unit in cycle I meeting I was 72% and in cycle II meeting I was found to be an increase of 91%. The conclusion of the study is that through various puzzle media from used materials can increase the recognition of geometry in group B children in the LAGAN PERTIWI PAUD Unit in group B, West Seluma District, Seluma Regency, it is proven that in cycle II there was a significant increase, the percentage of achievement results was 99% with very developed criteria. good (BSB).